THE COOPERATIVE DEVELOPMENT SUPERVISIONS STUDENT QUALITY GUIDELINES IN HUASAI INDUSTRIAL AND COMMUNITY EDUCATION COLLEGE UNDER OFFICE OF THE VOCATIONAL EDUCATION COMMISSION - Kudkeaw, Chotikarn; Sumato, Phramaha Supot; Yotharak, Maliwan (Journal of MCU Nakhondhat, 2023)
The objectives of this research are: 1) to study the condition of learning the cooperative development supervisions student quality guidelines in Huasai industrial and community education college. 2)to study the cooperative development supervision student quality guidelines in Huasai Industrial and community education college.3) to present the cooperative development supervision student quality guidelines in Huasai Industrial and community education college. This research is qualitative research. The data were collected through in-depth interviews with 17 people. 5 key informants and a focus group of 7 experts. The statistic used content analysis. The results showed that 1. The learning condition has a meeting to examine the learning management plan and evaluate the report as seen by the supervision at the time of entering the teaching supervision. The supervision recipients had a bad attitude toward supervision are not used as information to improve the quality of learners. 2. The result of the cooperative development supervisions student quality guidelines has 5steps as follows:1) Planning-P 2) Informing - 3) Doing - D 4) Evaluation - E and 5) capability and responsibility application.3.The implementation of supervision focuses on monitoring the teaching process to develop the quality of learners, which consists of 4 components: 1) morality, ethics, and desirable characteristics,2) knowledge3) skills, and 4) capability and responsibility application.